A Longitudinal Study on Campylobacter spp. in an Integrated Broiler Complex in the Southeast Region of the United States: Prevalence and Phylogenetic Analysis - Yagya Adhikari; Matthew A. Bailey; Dianna V. Bourassa; Sabin Poudel; Richard J. Buhr; Kenneth S. Macklin (Journal of Food Protection)
Poultry meat products are considered the major contributors to Campylobacteriosis in humans. The objective of this study was to determine the prevalence status, critical entry points, and movement patterns of Campylobacter spp. along different stages of an integrated broiler complex. To isolate bacteria and perform phylogenetic analysis, a total of 790 environmental samples were collected from 38 production houses, a hatchery, 6 transport trucks, and a processing plant of a commercial broiler complex. Odds ratio and 95% confidence intervals were compared among different stages and sample types (α = 0.05). Altogether 17% (137/790) of samples and 61% (23/38) of production houses were positive for Campylobacter spp. Similarly, 34% (46/135) of samples were identified as Campylobacter jejuni (C. jejuni), and 61% (83/135) were identified as Campylobacter coli (C. coli). The odds of Campylobacter spp. detection in broiler farms’ surroundings were 4 times (1.88–8.26; 95% CLs) more likely as compared to parent pullets and breeder farms’ surroundings (p = 0.0004). Similarly, among different sample types, the odds of Campylobacter spp. detection in boot swabs and sponge-stick swabs were more likely as compared to fly paper samples (p ≤ 0.0024). In addition, the odds of Campylobacter spp. detection in postpick whole carcass rinses were 4 times (1.99–7.59; 95% CLs) more likely as compared to postchill carcass rinses (p = 0.0004). The phylogeny results of both C. jejuni and C. coli indicate multiple critical entry points of bacterial strains along the chain and suggest the possibility of transmission of Campylobacter spp. from broiler grow-out flocks through transport and to final raw products (29%) in the processing plant. The results indicate potential risks of foodborne infections in consumers from ingestion of contaminated raw or undercooked poultry meat. Therefore, a comprehensive control strategy may be essential to reduce or eliminate Campylobacter spp. or other zoonotic pathogens from the poultry food chain.